The Extent of Application of Science's Teachers to the Habits of Mind to improve the learning of Secondary School Students in Holy Makkah - Subehi, Nisreen Hasan (Journal of Educational and Psychological Sciences, 2020)
The study aimed to know the extent of applying science teachers the habits of mind to develop learning of secondary school students in Holy Makkah, for this purpose a survey descriptive approach was applied that relies on data collection and tabulation and then analyzing and extracting results from it, to determine the extent of application, prepare a questionnaire, and submit the proposed recommendations. The sample of the study was (31) female science teachers for the secondary stage.In order to answer the study questions, a questionnaire was applied (prepared by the researcher) that consists of four axes of mind habits, aiming to know the extent of applying the parameters to mind habits to develop the learning of high school students. (T-test - correlation coefficient). The results confirmed that secondary school teachers apply some mind habits to develop their students ’learning at an average rate of 50.76%. The study recommended the importance of holding training courses for female teachers in various stages of education on habits of the mind, and focusing on the use of learning based on habits of the mind, to move from teaching information to teaching effective skills and strategies for the learning process.
Keywords: Habits of Mind; Secondary school teachers; Secondary school science courses; Learning development